COVID-19 in Brazil—Preliminary Analysis of Response Supported by Artificial Intelligence in Municipalities - Morales, Hugo M. P.; Guedes, Murilo; Silva, Jennifer S.; Massuda, Adriano (Frontiers in Digital Health, 2021)
The COVID-19 pandemic seriously challenged health systems worldwide and forced rapid adaptations in healthcare delivery and coordination, opening opportunities for innovation, especially for the use of digital health use of Artificial Intelligence (AI). Although Brazil has a universal and decentralised public health system, deficiencies in its structure and governance have hampered an effective response to the pandemic. To increase management capacity at a municipal level, we developed a platform powered by Artificial Intelligence, called Laura Digital Emergency Room. By providing an innovative way for to patients have easy access to medical information via telemedicine, the platform offers a solution to triage patients and monitor the evolution of symptoms. In the present study we describe a case report analysing the use of Laura Digital ER in three different cities. It was computed around 130,000 interactions made by the chatbot and 24,162 patients completed the digital triage. Almost half (44.8%) of the patients were classified as having mild symptoms, 33.6% were classified as moderate and only 14.2% were classified as severe. Marketing strategy seems to play a fundamental roll in the adhesion of tool by the population. Our experience is an opportunity to discuss the achievements, challenges, and potential uses of digital health in the Brazilian health system in a public health emergency context.